Design and simulate an amine-based CO2 capture process for a steam methane reforming hydrogen production plant - Hamed, Ali Mahmoud; Tuan Kamaruddin, Tengku Nordayana Akma; Ramli, Nabilah; Abd. Wahab, Mohd. Firdaus (Institute of Physics, 2023)
Steam methane reforming (SMR) is a common technique for hydrogen production, however CO2, which is created as a by-product, needs to be captured. Chemical absorption utilizing amine solvents is the most economically practical method of CO2 capturing. Amines are a class of organic compounds that are commonly used as chemical solvents for carbon capture. The effectiveness of a particular amine as a carbon capture solvent depends on its chemical structure and properties. Some commonly used amines for carbon capture include monoethanolamine (MEA), diethanolamine (DEA), and methyldiethanolamine (MDEA). This study aims to simulate SMR hydrogen production plant utilizing amine-based carbon dioxide capture system using Aspen HYSYS V11 software and figure out the efficiency of different chemical solvents in capturing carbon dioxide. The results of this study show that MEA has high efficiency to capture CO2 due to its high reactivity and ability to form a strong chemical bond with CO2. However, it is also highly corrosive and can be costly to regenerate.